(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Clinical guidelines recommend that optimal management of Non ST Elevation Acute Coronary Syndrome (NSTE-ACS) should include patient risk stratification. Predicting the anatomical extension of Coronary Artery Disease (CAD) is also potentially useful for clinical decision. The objective of our study was to determine whether the TIMI risk score correlates with the angiographic extent and severity of CAD in patients with NSTE- ACS. Materials and methods: This cross-sectional study was carried out in the Department of Cardiology, Chittagong Medical College Hospital (CMCH) on a total of 200 patients diagnosed with NSTE - ACS. TIMI risk score was calculated for each patient and they were stratified into 3 groups according to the TIMI risk score: low risk (0-2) intermediate risk (3-4) high risk (5-7). The severity of the CAD was assessed by Gensini score. Results: Mean (± SD) age was 53.7 (±10.8) years and 142 (71%) were male. Regarding cardiovascular risk factors, 68.5% had diabetes mellitus, 41.5% had dyslipidaemia, 77.5% had hypertension, 68% were current smoker and 35% had a family history of CAD. The Gensini score was higher in patients at high risk TIMI group. Moreover, there was a signi cant positive correlation between the TIMI and Gensini score (r=0.446). TIMI score can predict significant CAD moderately well (Area under the curve 0.661). Significantly higher proportion of patients with TIMI score more than 4 (65.9%) had significant three vessels CAD compared to patients with TIMI risk score 3-4 (17.9%) and TIMI risk score less than 3 (2%). Conclusion: TIMI score had good predictive value in assessment the severity of CAD in patients with NSTE-ACS JCMCTA 2021 ; 32 (1) : 26-30